2023
DOI: 10.1186/s12904-023-01142-3
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives across Canada about implementing a palliative approach in long-term care during COVID-19

Abstract: Background Long-term care (LTC) homes have been disproportionately impacted during COVID-19. Purpose To explore the perspectives of stakeholders across Canada around implementing a palliative approach in LTC home during COVID-19. Methods Qualitative, descriptive design using one-to-one or paired semi-structured interviews. Results Four themes were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…Some of the study findings are similar to those reported in previous publications across several countries. 22 – 28 The heightened distress of health care professionals caused by the COVID-19 pandemic, for example, has been reported by others. 29 , 30 However, to our knowledge, the previously published studies did not describe detailed accounts and experiences of long-term care clinicians working and providing end-of-life care in long-term care homes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Some of the study findings are similar to those reported in previous publications across several countries. 22 – 28 The heightened distress of health care professionals caused by the COVID-19 pandemic, for example, has been reported by others. 29 , 30 However, to our knowledge, the previously published studies did not describe detailed accounts and experiences of long-term care clinicians working and providing end-of-life care in long-term care homes.…”
Section: Discussionmentioning
confidence: 90%
“…These strategies have previously been emphasized by experts and researchers in the field. 3 , 7 , 10 , 28 , 32 , 35 – 37…”
Section: Discussionmentioning
confidence: 99%